Human extracellular superoxide dismutase (EC-SOD) expression in transgenic chicken - Sung June Byun; Mi-Ran Ji; Ye-Jin Jang; A-In Hwang; Hee Kyoung Chung; Jeom Sun Kim; Kyung-Woon Kim; Hak-Jae Chung; Byoung-Chul Yang; Iksoo Jeon; Jin-Ki Park; Jae Gyu Yoo; et al. (BMB Reports, 2013)
Extracellular superoxide dismutase (EC-SOD) is a metalloproteinand functions as an antioxidant enzyme. In this study,we used lentiviral vectors to generate transgenic chickens thatexpress the human EC-SOD gene. The recombinant lentiviruseswere injected into the subgerminal cavity of freshly laideggs. Subsequently, the embryos were incubated to hatchusing phases II and III of the surrogate shell ex vivo culturesystem. Of 158 injected embryos, 16 chicks (G0) hatched andwere screened for the hEC-SOD by PCR. Only 1 chick wasidentified as a transgenic bird containing the transgene in itsgermline. This founder (G0) bird was mated with wild-typehens to produce transgenic progeny, and 2 transgenic chicks(G1) were produced. In the generated transgenic hens (G2),the hEC-SOD protein was expressed in the egg white andshowed antioxidant activity. These results highlight thepotential of the chicken for production of biologically activeproteins in egg white. [BMB Reports 2013; 46(8): 404-409]